Synthesis of polycrystalline YAIO 3 (YAP) by the solution combustion process - Lazo, A. (2017)
The solution‐combustion process is presented, as well as its application to the synthesis of YAlO3 (YAP). Urea and glycine were used as fuel for the combustion reaction and synthesis of the YAP. The structure and morphology of the obtained sample were analyzed using the X‐ray diffraction (XRD) powder method and scanning electron microscopy (SEM). The X‐ray patterns showed an excellent agreement with data reported in the literature for this material. Results are also given for samples of YAlxCrx‐1O3 doped with Cr3+, with x = 0.001, 0.01, which showed dominant diffraction peaks due to the orthorhombic phase of YAlO3.